Acrylate copolymers for galenical applications.
Modified acrylate copolymers with α-hydroxycarboxylic acid residues address the slow dissolution of existing pharmaceutical coatings by enhancing solubility at lower pH, ensuring timely release of active ingredients in the duodenum.
Patent Information
- Application Number
- JP2021529061
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-22
- Filing Date
- 2019-10-10
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2039-10-10
AI Technical Summary
Existing acrylate copolymers used in pharmaceutical coatings, such as Eudragit®, dissolve too slowly in the duodenum, leading to inefficient release of active ingredients and site-specific targeting issues, particularly for drugs absorbed primarily in this region of the gastrointestinal tract.
Synthesis of acrylate copolymers modified with α-hydroxycarboxylic acid residues, such as glycolic or lactic acid, which are incorporated into the polymer backbone through protected monomers and subsequently deprotected to enhance solubility, allowing for faster dissolution at lower pH values.
The modified copolymers exhibit increased solubility at pH 4-5, facilitating faster release of active ingredients in the duodenum, thereby improving therapeutic efficacy and reducing gastric side effects.
Smart Images

Figure 0007602800000128 
Figure 0007602800000129 
Figure 0007602800000130
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for preparing an acrylate copolymer, the acrylate copolymer produced by the method, and its use for pharmaceutical formulations and coatings. [Background technology]
[0002] The prior art contains known acrylate polymers for pharmaceutical applications. For example, Evonik Industries AG and BASF SE supply acrylate copolymers for tablet coating under the product names Eudragit® and Kollicoat®. Table 1 contains an overview of the various Eudragit® copolymers.
[0003] [Table 1]
[0004] DE 102005010108 A1 relates to water-soluble polymers for cosmetic or pharmaceutical use, copolymers having monomer units (m1) and (m2), where (m1) is selected from acrylic acid, methacrylic acid, ethacrylic acid, α-chloroacrylic acid, crotonic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, glutaconic acid, aconitic acid and mixtures thereof, and (m2) has the following structure: [ka] The present invention discloses a copolymer having the following formula:
[0005] EP 2 679 216 B1 discloses a core-shell tablet for multiphasic release of betahistine, having an intermediate membrane disposed between the core and the shell, comprising a film former composed of cellulose derivatives, methacrylic acid polymers, polyvinyl derivatives and mixtures thereof, the core and / or the shell preferably containing an α-hydroxycarboxylic acid as a buffering agent.
[0006] WO2015 / 000970A1 relates to a method, polymers synthesized by the method and their use in pharmaceutical formulations. In the method, α,β-ethylenically unsaturated carboxylic acids, sulfonic acids and / or phosphonic acids and cross-linking monomers are copolymerized with a polyether component by free radical polymerization. Some of the resulting copolymers are composed of polyacrylic acid and polyether.
[0007] Furthermore, DE 69510190T2 describes a bioadhesive (or mucoadhesive) pharmaceutical composition in the form of a spray comprising a fatty acid ester having saturated or unsaturated fatty acids with a total number of 8 to 22 carbon atoms, the fatty acid ester being selected from fatty acid esters of polyhydric alcohols, fatty acid esters of hydroxycarboxylic acids, fatty acid esters of monosaccharides, fatty acid esters of glyceryl phosphate derivatives, fatty acid esters of glyceryl sulfate derivatives and mixtures of the aforementioned fatty acid esters.
[0008] Tablets are the most commonly used pharmaceutical form, with a market share approaching 50%. This is due to the fact that they are simple and inexpensive to manufacture and package, provide accurate dosage of active ingredients, have a long shelf life, and are easy for patients to store, handle, and take, which are associated with good therapeutic compliance. Furthermore, they are amenable to pressing a large number of active ingredients into tablet form using pharmaceutical auxiliaries.
[0009] The oral administration of medicines and their absorption in the digestive tract require a certain degree of hydrophilicity of the active ingredient, which is related to its water solubility. Tablet coatings are used to protect the tablet ingredients from moisture and external influences, as well as to mask the taste. Many active pharmaceutical ingredients are alkaloids and have an unpleasant bitter taste.
[0010] In the case of oral administration, it may be absolutely necessary to protect the active pharmaceutical ingredient from the harsh environment of the stomach. The pH of the stomach on an empty stomach is about 2, and with food it rises to values of 4.5 or higher. In the case of acid-sensitive active ingredients, for example omeprazole, this may cause irreversible changes. In many medicines (e.g. 5-aminosalicylic acid), the therapeutic objective is controlled by release at a given site in the digestive tract. Experts often refer to controlled release as "drug targeting". In addition, there are active ingredients (e.g. acetylsalicylic acid) that irritate the gastric mucosa, making a gastric juice-resistant coating necessary to reduce gastric side effects. The use of gastric juice-resistant coatings is not limited to tablets. Other oral formulations, for example capsules and granules, are also coated with gastric juice-resistant coatings. For gastric juice-resistant coatings, the use of weakly acidic copolymers that exist in protonated form and therefore have low solubility in the stomach is preferred. The market for pharmaceutical formulations and coatings has long been dominated by cellulose acetate phthalate (CAP), but more recently it is being replaced by methacrylic acid-ethyl acrylate copolymers.
[0011] Eudragit® polymers (Evonik Industries AG) are one of a family of acrylate copolymers developed in the 1950s for use as tablet coatings and tablet carrier materials. All Eudragit® polymers share the common feature of a polyacrylate or polymethacrylate backbone. Depending on the type, Eudragit® polymers differ in their side chain substitution patterns and solubility properties. Eudragit® analogue polymers are marketed under the product name Kollicoat® by BASF SE. Tablet coatings based on acrylate copolymers are characterized by mechanical stability, high water vapor barrier properties and acid stability.
[0012] According to manufacturer's data, the solubility of established acrylate copolymers increases rapidly above pH 5.5. However, in vivo studies have shown that solvation of tablet coatings based on acrylate copolymers and the associated release of active ingredients is too slow to target the duodenum (Cole, ET; Scott, RA; Connor, AL; Wilding, l. R.; Petereit, H.-U.; Schminke, C.; Beckert, T.; Cade, D. lnternational Journal of Pharmaceutics 2002, 231 (1), 83-95. DOI: 10.1016 / 50378-5173(01)00871-7; AI-Gousous, J.; Amidon, GL; Langguth, P. Molecular pharmaceutics 2016, 13 (6), 1927-1936; DOI: 10.1021 / acs.molpharmaceut.6b00077; Liu, F.; Basit, AW Journal of controlled release: official journal of the Controlled Release Society 2010, 147 (2), 242-245; DOI: 10.1016 / j.jconrel.2010.07.105). This is particularly problematic for active ingredients that are primarily absorbed in the duodenum.
[0013] Furthermore, therapeutic problems arise due to the lack of site-specific release of active ingredients. In this regard, the example of the enzyme pancreatin, which is administered to patients suffering from exocrine pancreatic insufficiency, can be mentioned. If the acid-degradable pancreatin is not released immediately downstream of the stomach, the lipids present in the food are not fully digested, which increases the possibility of causing intestinal upset. Summary of the Invention
[0014] In view of the above problems, there is a need for pharmaceutical coatings that dissolve more quickly after leaving the stomach than materials known in the prior art.
[0015] In the context of the method of the present invention, novel acrylate monomers of the Ayl-OR-OP or MAyl-OR-OP type were synthesized, where "Ayl" is acryloyl, "MAyl" is methacryloyl, "R" is the residue of an α-hydroxycarboxylic acid, and "P" is a protecting group. The α-hydroxycarboxylic acid is selected from the group consisting of hydroxyethanoic acid (glycolic acid), 2-hydroxypropanoic acid (lactic acid), 2-hydroxybutanoic acid, 2-hydroxyisobutanoic acid, 2-hydroxy-2-methyl-3-oxobutanoic acid, phenylhydroxyethanoic acid, 2-hydroxy-4-methylthiobutanoic acid, 2-hydroxybutane-1,4-dicarboxylic acid (malic acid), 2-hydroxypropanedicarboxylic acid, 2-hydroxypropane-1,2,3-tricarboxylic acid, hydroxypropane-1,2,3-tricarboxylic acid, or 2,3-dihydroxybutanedicarboxylic acid. and has the structure OH-R-OH, where R is -CH2(C=O), -CH(CH3)(C=O)-, -CH(CH2CH3)(C=O)-, -C(CH3)2(C=O)-, -C(CH3)(COCH3)(C=O)-, -CH(Ph)(C=O)-, -CH[(CH2)2SCH3](C=O)-, -CH(CH2COOH)(C=O)-, -CH(COOH)(C=O)-, -C(CH2COOH)2(C=O)-, -CH(COOH)CH(CH2COOH)(C=O)-, or -CH(COOH)(CHOH)(C=O)-. The protecting group P is a benzyl group (-CH2Ph), a tert-butyl group (-C(CH3)3), or an allyl group. In a preferred embodiment of the method of the present invention, the protected monomers synthesized are benzyl methacryloyloxyethanoate (MAylO-Gly-Bn), (2S)-2-benzyl methacryloyloxypropionate (MAylO-L-La-Bn) and (R,S)-2-benzyl methacryloyloxypropionate (MAylO-D,L-La-Bn).
[0016] The above protected monomers are copolymerized by free radical polymerization with methyl acrylate (MA), methyl methacrylate (MMA), ethyl acrylate (EA) or ethyl methacrylate (EMA) and optionally protected acrylic acid or protected methacrylic acid. The protecting group P is then removed from the synthesized copolymer by reduction. For example, in the case of P=Bn, the benzyl protecting group is replaced by heterogeneous palladium-catalyzed hydrogenolysis under a hydrogen atmosphere.
[0017] The esterification of α-hydroxycarboxylic acids with acrylic or methacrylic acid or with the functional sidearms of the Eudragit® family of polymers is carried out in three steps: (i) a step of introducing a protecting group, (ii) a step of esterification, and (iii) a step of deprotection, in order to avoid the formation of difunctional α-hydroxycarboxylic acid oligomers. First, in step (i), the carboxyl group of the α-hydroxycarboxylic acid is blocked with a protecting group, for example benzyl (Bn). The benzyl protecting group is stable to acids and bases and is removed by hydrolysis in step (iii) after esterification of the protected α-hydroxycarboxylic acid in step (ii).
[0018] [ka]
[0019] To take advantage of established acrylate copolymers for use as gastro-resistant tablet coatings, the approved Eudragit® polymer base structure has been built upon: the poly(meth)acrylate backbone is retained and the side chains are modified.
[0020] Quite unexpectedly, it was found that even minor modifications to established acrylate copolymers, such as the replacement of only a 5-20% fraction of the carboxyl OH groups by residues of α-hydroxycarboxylic acids, especially glycolic or lactic acid, significantly affect the solubility properties, shifting them towards lower pH values. The drastic change in the mechanism of action upon replacement of carboxyl groups by α-hydroxycarboxylic acid residues has not been satisfactorily elucidated so far. It is believed that at least some of the substitution sites increase the free volume due to steric effects, increasing the relaxivity (mobility) of the polymer chains. The substituents act like internal plasticizers.
[0021] The starting point is the hypothesis that a negative inductive effect acts on the carboxyl group of an α-hydroxycarboxylic acid substituent. The resonance structures in Scheme 2 show the inductive effect caused by the partial positive charge of the oxygen atom in the carboxyl group.
[0022] [ka]
[0023] The present invention encompasses the synthesis of copolymers having monomer units that include residues of α-hydroxy carboxylic acids, such as glycolic acid, L-lactic acid, or D,L-lactic acid. In a preferred embodiment, the copolymers of the present invention have structures that embody analog modifications of Eudragit® or Kollicoat® type acrylate copolymers.
[0024] A major advantage of the polymers of the invention is their good physiological compatibility. Hydrolysis of the ester bonds releases glycolic acid or lactic acid in the digestive tract. Lactic acid is an endogenous substance and is approved as a food additive (E 270). The toxicity of glycolic acid is very low and physiologically irrelevant.
[0025] Studies have shown that the polymers of the present invention have higher solubility at pH values of 4-5 than Eudragit® polymers.
[0026] For qualitative measurements of solubility, the polymers of the invention are suspended in a buffer solution at room temperature in a snap-top bottle at a concentration of 5 mg polymer per mL of buffer solution. Dissolution occurs within minutes (Table 2: + marks) or there is almost no dissolution even when suspended in the buffer solution for several days (Table 2: - marks).
[0027] [Table 2]
[0028] Eudragit® L 100 (Evonik Industries AG) and an analog polymer prepared by controlled free radical polymerization (CFRP) (referred to as "L 100 analog" or "MA-co-EA") have virtually identical solubility properties.
[0029] In contrast, Eudragit® polymers modified with α-hydroxycarboxylic acids, such as glycolic acid, L-lactic acid or D,L-lactic acid (types "MAylO-Gly-co-EA, "MAylO-L-La-co-EA" and "MAylO-D,L-La-co-EA") dissolve at a lower pH than known Eudragit® polymers and therefore provide the basis for gastric juice-resistant formulations with faster release and absorption of the active ingredient. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 shows an apparatus for measuring the solubility of a polymer as a function of pH. [Diagram 2] FIG. 2 shows the solubility measurements for Eudragit® L 100 and similar polymers of the invention. [Diagram 3]FIG. 3 shows the solubility measurements for Eudragit® L 100-55 and similar polymers of the invention. [Figure 4] FIG. 4 shows the release of paracetamol from capsules coated with Eudragit® L 100 and similar polymers. [Diagram 5] FIG. 5 shows the release of paracetamol from capsules coated with Eudragit® L 100-55 and similar polymers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Accordingly, it is an object of the present invention to provide polymers for pharmaceutical formulations that have different solubility characteristics than known acrylate copolymers.
[0032] The objective is to have the following structure: [ka] [In the formula, MA is the methyl acrylate residue (-CH[(C=O)OCH3]CH2-), MMA is the methyl methacrylate residue (-C(CH3)[(C=O)OCH3]CH2-) EA is the ethyl acrylate residue (-CH[(C=O)OCH2CH3]CH2-), EMA is the residue of ethyl methacrylate (-C(CH3)[(C=O)OCH2CH3]CH2-); AS is an acrylic acid residue (-CH[(C=O)-]CH2-), MAS is a methacrylic acid residue (-C(CH3)[(C=O)-]CH2-); R is -CH2(C=O)-, -CH(CH3)(C=O)-, -CH(CH2CH3)(C=O)-, -C(CH3)2(C=O)-, -C(CH3)(COCH3)(C=O)-, -CH(Ph)(C=O)-, -CH[(CH2)2SCH3]( C=O)-, -CH(CH2COOH)(C=O)-, -CH(COOH)(C=O)-, -C(CH2COOH)2(C=O)-, -CH(COOH)CH(CH2COOH)(C=O)- or -CH(COOH)(CHOH)(C=O)-; n is an integer of 1≦n≦20, and x, y, and z represent the relative molar ratios of monomer units, where 1≦x≦20, 1≦y≦20, and 0≦z≦20. This is achieved by a copolymer having the formula:
[0033] In a preferred embodiment of the present invention, The copolymer has the following structure: [ka] having; · n=1, n=2, n=3, n=4, n=5, n=6, n=7, n=8, n=9, n=10, n=11, n=12, n=13, n=14, n=15, n=16, n=17, n=18, n=19 or n=20; n=1, n=2 or n=3; x is a real number; 1≦x≦12 or 8≦x≦20; 1≦x≦6, 4≦x≦8, 6≦x≦10, 8≦x≦12, 10≦x≦14, 12≦x≦16, 14≦x≦18 or 16≦x≦20; 1≦x≦3, 2≦x≦4, 3≦x≦5, 4≦x≦6, 5≦x≦7, 6≦x≦8, 7≦x≦9, 8≦x≦10, 9≦x≦11, 10≦x≦12, 11≦x≦13, 12≦x≦14, 13≦x≦15, 14≦x≦16, 15≦x≦17, 16≦x≦18, 17≦x≦19 or 18≦x≦20; x=1, x=2, x=3, x=4, x=5, x=6, x=7, x=8, x=9, x=10, x=11, x=12, x=13, x=14, x=15, x=16, x=17, x=18, x=19 or x=20; · y is a real number; 1≦y≦12 or 8≦y≦20; 1≦y≦6, 4≦y≦8, 6≦y≦10, 8≦y≦12, 10≦y≦14, 12≦y≦16, 14≦y≦18 or 16≦y≦20; 1≦y≦3, 2≦y≦4, 3≦y≦5, 4≦y≦6, 5≦y≦7, 6≦y≦8, 7≦y≦9, 8≦y≦10, 9≦y≦11, 10≦y≦12, 11≦y≦13, 12≦y≦14, 13≦y≦15, 14≦y≦16, 15≦y≦17, 16≦y≦18, 17≦y≦19 or 18≦y≦20; · y=1, y=2, y=3, y=4, y=5, y=6, y=7, y=8, y=9, y=10, y=11, y=12, y=13, y=14, y=15, y=16, y=17, y=18, y=19 or y=20; z is a real number; z=0; 1≦z≦12 or 8≦z≦20; 1≦z≦6, 4≦z≦8, 6≦z≦10, 8≦z≦12, 10≦z≦14, 12≦z≦16, 14≦z≦18 or 16≦z≦20; 1≦z≦3, 2≦z≦4, 3≦z≦5, 4≦z≦6, 5≦z≦7, 6≦z≦8, 7≦z≦9, 8≦z≦10, 9≦z≦11, 10≦z≦12, 11≦z≦13, 12≦z≦14, 13≦z≦15, 14≦z≦16, 15≦z≦17, 16≦z≦18, 17≦z≦19 or 18≦z≦20; · z=1, z=2, z=3, z=4, z=5, z=6, z=7, z=8, z=9, z=10, z=11, z=12, z=13, z=14, z=15, z=16, z=17, z=18, z=19 or z=20; 0.8x≦y+z≦1.2x; 0.9x≦y+z≦1.1x; · y+z=x; 0.3x≦y+z≦.7x; 0.4x≦y+z≦0.6x; y+z=0.5x; y≦z≦6y, 5y≦z≦11y, 8y≦z≦14y, 11y≦z≦17y or 14y≦z≦20y; y≦z≦3y, 2y≦z≦4y, 3y≦z≦5y, 4y≦z≦6y, 5y≦z≦7y, 6y≦z≦8y, 7y≦z≦9y, 8y≦z≦10y, 9y≦z≦11y, 10y≦z≦12y, 11y≦z≦13y, 12y≦z≦14y, 13y≦z≦15y, 14y≦z≦16y, 15y≦z≦17y, 16y≦z≦18y, 17y≦z≦19y or 18y≦z≦20y; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; The copolymer has the following structure: [ka] having; R is -CH2(C=O)-; R is -CH(CH3)(C=O)-; The molar mass Mw of the copolymer is 4000 g mol -1 ≦Mw≦500000g mol -1 and; The molar mass Mw of the copolymer is 4000 g mol -1 ≦Mw≦30000g mol -1 , 20000 g·mol -1 ≦Mw≦60000g mol -1,40000g·mol -1 ≦Mw≦80000g mol -1 ,60000g·mol -1 ≦Mw≦100000g mol -1 ,80000g·mol -1 ≦Mw≦120000g mol -1 ,100000g·mol -1 ≦Mw≦140000g mol -1 ,120000g·mol -1 ≦Mw≦160000g mol -1 ,140000g·mol -1 ≦Mw≦180000g mol -1 ,160000g·mol -1 ≦Mw≦200000g mol -1 ,180000g·mol -1 ≦Mw≦220000g mol -1 ,200000g·mol -1 ≦Mw≦240000g mol -1 ,220000g·mol -1 ≦Mw≦260000g mol -1 ,240000g·mol -1 ≦Mw≦280000g mol -1 ,260000g·mol -1 ≦Mw≦300000g mol -1 ,280000g·mol -1 ≦Mw≦320000g mol -1 ,300000g·mol -1 ≦Mw≦340000g mol -1 ,320000g·mol -1 ≦Mw≦360000g mol -1 ,340000g·mol -1 ≦Mw≦380000g mol -1 ,360000g·mol -1 ≦Mw≦400000g mol -1 ,380000g·mol -1 ≦Mw≦420000g mol -1 ,400000g·mol -1 ≦Mw≦440000g mol -1, 420000 g mol -1 ≦Mw≦460000g mol -1 , 440000 g mol -1 ≦Mw≦480000g mol -1 or 460000 g mol -1 ≦Mw≦500000g mol -1 and; The polydispersity of the copolymer is
number
number
[0034] It is a further object of the present invention to provide a method for synthesizing polymers for pharmaceutical formulations that have different solubility characteristics than known acrylate copolymers.
[0035] The objective is to carry out the following steps: (a) selected from the group including hydroxyethanoic acid, 2-hydroxypropanoic acid, 2-hydroxybutanoic acid, 2-hydroxyisobutanoic acid, 2-hydroxy-2-methyl-3-oxobutanoic acid, phenylhydroxyethanoic acid, 2-hydroxy-4-methylthiobutanoic acid, 2-hydroxybutane-1,4-dicarboxylic acid, 2-hydroxypropanedicarboxylic acid, 2-hydroxypropane-1,2,3-tricarboxylic acid, hydroxypropane-1,2,3-tricarboxylic acid, or 2,3-dihydroxybutanedicarboxylic acid, and having the following structure: [ka] [In the formula, R is -CH2(C=O)-, -CH(CH3)(C=O)-, -CH(CH2CH3)(C=O)-, -C(CH3)2(C=O)-, -C(CH3)(COCH3)(C=O)-, -CH(Ph)(C=O)-, -CH[(CH2)2SCH3]( C=O)-, -CH(CH2COOH)(C=O)-, -CH(COOH)(C=O)-, -C(CH2COOH)2(C=O)-, -CH(COOH)CH(CH2COOH)(C=O)- or -CH(COOH)(CHOH)(C=O)-. ] with acrylic acid ((CH2)HC-COOH) or methacrylic acid ((CH2)(CH3)C-COOH) to give the following structure: [ka] [In the formula, "Ayl" is acryloyl ((CH2)HC-CO-), and "MAyl" is methacryloyl ((CH2)(CH3)C-CO-). obtaining a compound having the formula: (b) optionally monoesterifying or polyesterifying the compound (Ia) or (IIa) obtained in step (a) with an α-hydroxycarboxylic acid to obtain a compound having the following structure: [ka] [In the formula, 2≦m≦20.] obtaining a compound of formula (I); (c) conjugating the compound (Ia), (Ib), (IIa) or (IIb) obtained in step (a) or (b) with a protecting group P to obtain a compound having the following structure: [ka] [In the formula, 1≦n≦20.] obtaining a compound of formula (I); (d) optionally conjugating acrylic acid or methacrylic acid with a protecting group P to obtain protected acrylic acid ((CH2)HC-COOP) or protected methacrylic acid ((CH2)(CH3)C-COOP); (e) Polymerization of compound (Ic) or (IIc) in a relative molar ratio y with methyl acrylate, methyl methacrylate, ethyl acrylate or ethyl methacrylate in a relative molar ratio x and optionally with a protected acrylic acid or a protected methacrylic acid in a relative molar ratio z to give the following type: [ka] [In the formula, MA is the methyl acrylate residue (-CH[(C=O)OCH3]CH2-), MMA is the methyl methacrylate residue (-C(CH3)[(C=O)OCH3]CH2-) EA is the ethyl acrylate residue (-CH[(C=O)OCH2CH3]CH2-), EMA is the residue of ethyl methacrylate (-C(CH3)[(C=O)OCH2CH3]CH2-); AS is an acrylic acid residue (-CH[(C=O)-]CH2-), MAS is a methacrylic acid residue (-C(CH3)[(C=O)-]CH2-); 1≦x≦20, 1≦y≦20, and 0≦z≦20. obtaining a copolymer of the formula (1); and (f) deprotecting and hydrolyzing the copolymer obtained in step (e) to obtain a copolymer of the following type: [ka] A process for obtaining a copolymer of This is achieved by a method comprising:
[0036] A preferred embodiment of the method comprises the steps of: in step (a), protecting the α-hydroxycarboxylic acid with a protecting group P, followed by esterification with acrylic acid or methacrylic acid, and removing the protecting group P after esterification; When step (b) is carried out once or several times, the α-hydroxycarboxylic acid is protected by a protecting group P, and then the compound Ayl-(OR) q -OH or MAyl-(OR) q esterification with -OH and removal of the protecting group P after esterification; the protecting group P is selected from the group comprising the benzyl group (-CH2Ph), the tert-butyl group (-C(CH3)3) and the allyl group; In step (e), carrying out a free radical polymerization; In step (e), carrying out RAFT polymerization (reversible addition-fragmentation chain transfer polymerization) using a chain transfer agent; in step (e), carrying out RAFT polymerization (reversible addition-fragmentation chain transfer polymerization) using a chain transfer reagent selected from the group comprising dithioesters and trithiocarbonates; the deprotection and hydrolysis in step (f) is carried out using a catalyst; the deprotection and hydrolysis in step (f) is carried out under high pressure in the range of 5 to 100 bar; n=1, n=2, n=3, n=4, n=5, n=6, n=7, n=8, n=9, n=10, n=11, n=12, n=13, n=14, n=15, n=16, n=17, n=18, n=19 or n=20; n=1, n=2 or n=3; x is a real number; 1≦x≦12 or 8≦x≦20; 1≦x≦6, 4≦x≦8, 6≦x≦10, 8≦x≦12, 10≦x≦14, 12≦x≦16, 14≦x≦18 or 16≦x≦20; 1≦x≦3, 2≦x≦4, 3≦x≦5, 4≦x≦6, 5≦x≦7, 6≦x≦8, 7≦x≦9, 8≦x≦10, 9≦x≦11, 10≦x≦12, 11≦x≦13, 12≦x≦14, 13≦x≦15, 14≦x≦16, 15≦x≦17, 16≦x≦18, 17≦x≦19 or 18≦x≦20; x=1, x=2, x=3, x=4, x=5, x=6, x=7, x=8, x=9, x=10, x=11, x=12, x=13, x=14, x=15, x=16, x=17, x=18, x=19 or x=20; · y is a real number; 1≦y≦12 or 8≦y≦20; 1≦y≦6, 4≦y≦8, 6≦y≦10, 8≦y≦12, 10≦y≦14, 12≦y≦16, 14≦y≦18 or 16≦y≦20; 1≦y≦3, 2≦y≦4, 3≦y≦5, 4≦y≦6, 5≦y≦7, 6≦y≦8, 7≦y≦9, 8≦y≦10, 9≦y≦11, 10≦y≦12, 11≦y≦13, 12≦y≦14, 13≦y≦15, 14≦y≦16, 15≦y≦17, 16≦y≦18, 17≦y≦19 or 18≦y≦20; · y=1, y=2, y=3, y=4, y=5, y=6, y=7, y=8, y=9, y=10, y=11, y=12, y=13, y=14, y=15, y=16, y=17, y=18, y=19 or y=20; z is a real number; z=0; 1≦z≦12 or 8≦z≦20; 1≦z≦6, 4≦z≦8, 6≦z≦10, 8≦z≦12, 10≦z≦14, 12≦z≦16, 14≦z≦18 or 16≦z≦20; 1≦z≦3, 2≦z≦4, 3≦z≦5, 4≦z≦6, 5≦z≦7, 6≦z≦8, 7≦z≦9, 8≦z≦10, 9≦z≦11, 10≦z≦12, 11≦z≦13, 12≦z≦14, 13≦z≦15, 14≦z≦16, 15≦z≦17, 16≦z≦18, 17≦z≦19 or 18≦z≦20; · z=1, z=2, z=3, z=4, z=5, z=6, z=7, z=8, z=9, z=10, z=11, z=12, z=13, z=14, z=15, z=16, z=17, z=18, z=19 or z=20; 0.8x≦y+z≦1.2x; 0.9x≦y+z≦1.1x; · y+z=x; 0.3x≦y+z≦0.7x; 0.4x≦y+z≦0.6x; · y+z=0.5x; y≦z≦6y, 4y≦z≦11y, 8y≦z≦14y, 11y≦z≦17y or 14y≦z≦20y; and / or y≦z≦3y, 2y≦z≦4y, 3y≦z≦5y, 4y≦z≦6y, 5y≦z≦7y, 6y≦z≦8y, 7y≦z≦9y, 8y≦z≦10y, 9y≦z≦11y, 10y≦z≦12y, 11y≦z≦13y, 12y≦z≦14y, 13y≦z≦15y, 14y≦z≦16y, 15y≦z≦17y, 16y≦z≦18y, 17y≦z≦19y or 18y≦z≦20y It is characterized by:
[0037] As an alternative to the above-mentioned "ab initio" synthesis methods, the present invention further provides methods of synthesis of the following type: [ka] A method for conjugating a known acrylate copolymer having stoichiometric or random repeat units of the formula (I) with v molar parts of an unprotected α-hydroxycarboxylic acid or an α-hydroxycarboxylic acid protected by a protecting group P, the α-hydroxycarboxylic acid being selected from the group consisting of hydroxyethanoic acid, 2-hydroxypropanoic acid, 2-hydroxybutanoic acid, 2-hydroxyisobutanoic acid, 2-hydroxy-2-methyl-3-oxobutanoic acid, phenylhydroxyethanoic acid, 2-hydroxy-4-methylthiobutanoic acid, 2-hydroxy-1-methyl-2-oxo ... and having the structure OH-R-OH or OH-RP, where u, v, w are real numbers with 1≦u≦20; 1≦w≦20; 1≦v≦w, and where in the case of using a protected α-hydroxy carboxylic acid, the protecting group P is removed in a further process step.
[0038] where R and P have the same meaning as above, i.e. R is -CH2(C=O)-, -CH(CH3)(C=O)-, -CH(CH2CH3)(C=O)-, -C(CH3)2(C=O)-, -C(CH3)(COCH3)(C=O)-, -CH(Ph)(C=O)-, -CH[(CH2)2SCH3](C=O)-, -CH(CH2COOH)(C=O)-, -CH(COOH)(C=O)-, -C(CH2COOH)2(C=O)-, -CH(COOH)CH(CH2COOH)(C=O)-, or -CH(COOH)(CHOH)(C=O)-; and P is a benzyl (-CH2Ph), tert-butyl (-C(CH3)3) or allyl group.
[0039] A preferred embodiment of the method for modifying known acrylate copolymers with unprotected or protected α-hydroxy carboxylic acids comprises the steps of: Use of glycolic acid as the α-hydroxycarboxylic acid; Use of lactic acid as the α-hydroxycarboxylic acid; 0.8u≦w≦1.2u; 0.3u≦w≦0.7u; v≦w≦6v, 5v≦w≦11v, 8v≦w≦14v, 11v≦w≦17v or 14v≦w≦20v; v≦w≦3v, 2v≦w≦4v, 3v≦w≦5v, 4v≦w≦6v, 5v≦w≦7v, 6v≦w≦8v, 7v≦w≦9v, 8v≦w≦10v, 9v≦w≦11v, 10v≦w≦12v, 11v≦w≦13v, 12v≦w≦14v, 13v≦w≦15v, 14v≦w≦16v, 15v≦w≦17v, 16v≦w≦18v, 17v≦w≦19v or 18v≦w≦20v, Use of DIPC (diisopropylcarbodiimide) as a coupling reagent. Use of DMAP (4(N,N-dimethylamino)pyridine) as a catalyst; and / or Carrying out the reaction in an organic solvent, e.g., benzene, dioxane or DMF It is characterized by:
[0040] This polymer-analogous method can be carried out for copolymers of any molecular weight: Eudragit L100 has a molecular weight of about 125,000 g / mol, and Eudragit L100-55 has a molecular weight of about 320,000 g / mol. These copolymers are prepared by suspension or emulsion polymerization and can be subjected to polymer-analogous modification in additional reaction steps, as described above.
[0041] The invention further relates to copolymers preparable by one of the processes described above.
[0042] The present invention further relates to the use of the above-mentioned copolymers for the preparation of pharmaceutical formulations, for the preparation of coatings for tablets or for capsules.
[0043] In the context of the present invention, the abbreviations "AS" and "MAS" used for acrylic acid residues (AS = -CH[(C=O)-]CH-) and methacrylic acid residues (MAS = -C(CH)[(C=O)-]CH-) and monomers containing these residues have the following meanings: [AS-OH] has -CH[(C=O)-OH]CH-; [MAS-OH] has -C(CH3)[(C=O)-OH]CH2-; [AS-(OR) n -OH] is -CH[(C=O)-(OR) n -OH]CH2-; [MAS-(OR) n -OH] is -C(CH3)[(C=O)-(OR) n -OH]CH2-.
[0044] The α-hydroxycarboxylic acids used in the context of the present invention are given in Table 3 below.
[0045] [Table 3]
[0046] Table 3 identifies the residue R for each of the α-hydroxy carboxylic acids from which the side arms of the copolymers of the invention are essentially formed. The side arms comprise from 1 to 20 residues R.
[0047] In a preferred embodiment of the invention, the stoichiometric or statistical repeat units of the acrylate copolymer have the following structure: [ka] has.
[0048] In the repeating unit of Scheme 2a, x, y, and z are as follows: 1≦x≦20, 1≦y≦20, 1≦z≦20; 0.8x≦y+z≦1.2x or 0.3x≦y+z≦0.7x; y≦z≦6y, 5y≦z≦11y, 8y≦z≦14y, 11y≦z≦17y or 14y≦z≦20y; and / or y≦z≦3y, 2y≦z≦4y, 3y≦z≦5y, 4y≦z≦6y, 5y≦z≦7y, 6y≦z≦8y, 7y≦z≦9y, 8y≦z≦10y, 9y≦z≦11y, 10y≦z≦12y, 11y≦z≦13y, 12y≦z≦14y, 13y≦z≦15y, 14y≦z≦16y, 15y≦z≦17y, 16y≦z≦18y, 17y≦z≦19y or 18y≦z≦20y Represents a real number that satisfies.
[0049] residue R 1 , R 2 , R 3 , R 4 , R 5 is independently -H or -CH3.
[0050] In a particularly preferred embodiment of the present invention, the residue R in the repeat unit shown in Scheme 2a 3 and R 5 are the same, i.e., R 3 =R 5 =-H or R 3 =R 5 =-CH3. R 3 =R 5 The acrylate copolymer according to Scheme 2a, (a') copolymerizing methyl acrylate, methyl methacrylate, ethyl acrylate or ethyl methacrylate with unprotected or protected acrylic acid or methacrylic acid; (b') deprotecting the acrylate copolymer obtained in step (a') if protected acrylic acid or protected methacrylic acid was used in step (a'); (c') esterifying the acrylate copolymer obtained in step (a') or (b') with protected glycolic acid or protected lactic acid; and (d') a step of deprotecting the acrylate copolymer obtained in step (c') It is synthesized by a simple method having the following formula: EXAMPLES
[0051] The present invention will now be described in detail with reference to examples, in which the subscripts n, x and y have definitions independent of the above description and claims.
[0052] Example 1: Synthetic strategy for acrylate copolymers containing α-hydroxycarboxylic acid residues α-Hydroxycarboxylic acids are bifunctional. Direct esterification of α-hydroxycarboxylic acids with acrylic or methacrylic acid therefore leads to a mixture of different oligomers. To prevent this, the acid groups are reversibly protected. Suitable protecting groups for this purpose include benzyl, tert-butyl or allyl groups, because they are easy to introduce and stable to the reaction conditions in the subsequent process steps. The protected α-hydroxycarboxylic acids can be conjugated with acrylic or methacrylic acid in a Stöcklich esterification to obtain monomers. The resulting monomers are copolymerized with methyl methacrylate or ethyl acrylate, and then the protecting groups are removed. This synthesis method is shown in Scheme 3.
[0053] [ka]
[0054] After polymerization, the protecting groups are removed by reduction with hydrogen using a palladium / charcoal catalyst.
[0055] Example 2: Modification of acrylate copolymers Scheme 4 shows a synthetic strategy for modifying an acrylate copolymer with a protected α-hydroxy carboxylic acid, for example, benzyl-protected glycolic acid (benzyl hydroxyethanoate or "Gly-Bn").
[0056] [ka]
[0057] Example 3: The principle of Stecklich esterification Scheme 5 illustrates the principle of the Stoecklich esterification utilized in the context of the present invention for the simple or repetitive conjugation of acrylic or methacrylic acid with protected alpha-hydroxycarboxylic acids.
[0058] [ka]
[0059] In general, esterification reactions involve the reaction of an organic acid with an alcohol to produce an ester. The acid has low carbonyl activity, so the reaction with the alcohol is slow. As the reactants fill the space, the reaction rate decreases. Carbonyl activity is generally improved by using carbonyl chlorides and carboxylic anhydrides. However, considering the reactants used in the present invention, carbonyl chlorides are not suitable.
[0060] In the present invention, it is preferred to use the principle of the Stäcklich esterification. Stäcklich esterification provides good yields under mild reaction conditions. Preferably, the coupling reagent used is DIPC (diisopropylcarbodiimide) and the catalyst used is DMAP (4(N,N dimethylamino)pyridine). The reaction mechanism is shown in Scheme 5. First, DIPC is combined with an acid to form an O-acylisourea, whose carbonyl activity is equivalent to that of the anhydride of the acid. DMAP is a stronger nucleophile than the alcohol used and combines with the acylisourea to form N,N' diisopropylurea and a reactive amide, also called "active ester". The latter, together with an alcohol and DMAP, which can also be used as an acyl transfer reagent, forms one of the esters provided according to the present invention.
[0061] Example 4: Principle of RAFT Polymerization The polymers of the invention are suitably copolymerized according to the RAFT principle, as shown in Scheme 6. RAFT polymerization is a method for the synthesis of polymers with narrow molecular weight distributions. For this purpose, in addition to the solvent, monomers and initiators, so-called chain transfer agents are added to the reaction solution, which react with the free radical chains in kinetic equilibrium and deactivate them. Suitable chain transfer agents are in particular dithioesters and trithiocarbonates.
[0062] [ka]
[0063] The initiators used are conventional initiators, for example AIBN (azoisobutyronitrile) or dibenzoyl peroxide. These split into reactive free radicals and then react with the monomers used. After the initiation reaction or initialization, the chains grow according to a free radical mechanism. When the free radical end of the growing molecular chain meets the chain transfer reagent, an addition radical is formed. This is temporarily in equilibrium between the polymer dithioester and the free radical R. The free radical R can initiate the formation of new free radical chains. The initial RAFT equilibrium is between the polymer dithioester and further free radical chains. The addition radical does not react with the monomers and is called the "sleeping" species. This significantly reduces the concentration of active free radicals. Due to the kinetic equilibrium, all chains have the same average growth time and achieve the same degree of polymerization. The polydispersity achieved in RAFT polymerization is in the range of 1.1 to 1.3.
[0064] The polymers of the present invention are preferably synthesized by RAFT polymerization in order to obtain low polydispersity associated with desired solubility properties. Furthermore, the chain transfer reagents used in RAFT polymerization allow the introduction of groups that have an NMR signature. By utilizing this NMR signature, the total number of monomers in the polymer chain can be determined.
[0065] Example 5: Hydroxyethanoate benzyl ester (Gly-Bn) Reaction Equation
[0066] [ka]
[0067] reaction
[0068] [Table 4]
[0069] procedure In a 250 mL one-neck flask, glycolic acid was dissolved in 150 mL of methanol and, while stirring, 1,8-diazabicyclo[5.4.0]undec-7-ene was added dropwise via a syringe. After stirring for 30 minutes, methanol was removed under reduced pressure at 50°C. The resulting oily liquid was dissolved in 240 mL of TV,TV-dimethylformamide and cooled to 5°C, and then benzyl bromide was added slowly via a dropping funnel while stirring. The solution was stirred at room temperature for 18 hours. To the solution were added 250 mL of ethyl acetate and 400 mL of water. The aqueous phase was then extracted four times by shaking with 150 mL of ethyl acetate each time. The combined organic phase was washed with 150 mL of water, three times with 100 mL of 5% citric acid, two times with 150 mL of saturated aqueous sodium chloride solution, and then dried with aqueous sodium sulfate solution. Ethyl acetate was removed under reduced pressure at 50°C. Hydroxyethanoate benzyl ester, 1×10 -3 Purification was performed by fractional distillation at 98°C and bar.
[0070] Characterization Appearance: Colorless liquid Yield: 51.11g, 0.3076mol, 78% Boiling point: 1×10 -3 98°C at bar M = 166.17 g / mol
[0071] [ka]
[0072] 1 H NMR:(400MHz;CDCl3):δ[ppm]=2.36(s,1H,Ha),4.20(s,2H,Hb),5.24(s,2H,Hc),7.34-7.40(m,5H,Hd)
[0073] Example 6: (S)-2-Hydroxypropionate benzyl ester (L-La-Bn) Reaction Equation
[0074] [ka]
[0075] reaction
[0076] [Table 5]
[0077] procedure The procedure was similar to the synthesis of hydroxyethanoate benzyl ester.
[0078] Characterization Appearance: Colorless liquid Yield: 34.66g, 0.1923mol, 71.6% Boiling point: 1×10 -3 96°C at bar M = 180.20 g / mol
[0079] [ka]
[0080] 1 H NMR:(400MHz;CDCl3):δ[ppm]=1.44(d,3H,Ha),2.83(s,1H,Hc),4.32(q,1H,Hb),5.21(s,2H,Hd),7.33-7.40(m,5H,He)
[0081] Example 7: 2-Hydroxypropionate benzyl ester (D,L-La-Bn) Reaction Equation
[0082] [ka]
[0083] reaction
[0084] [Table 6]
[0085] procedure The procedure was similar to the synthesis of hydroxyethanoate benzyl ester.
[0086] Characterization Appearance: Colorless liquid Yield: 13.02g, 0.0723mol, 65.1% Boiling point: 4.8×10 -3 91°C at bar
[0087] [ka]
[0088] 1 H NMR:(400MHz;CDCl3):δ[ppm]=1.44(d,3H,Ha),2.77(s,1H,Hc),4.32(q,1H,Hb),5.22(s,2H,Hd),7.32-7.41(m,5H,He)
[0089] Example 8: 2-Methacryloyloxyethanoate benzyl ester (MAylO-Gly-Bn) Reaction Equation
[0090] [ka]
[0091] reaction
[0092] [Table 7]
[0093] procedure Gly-Bn, methacrylic acid, and DMAP were transferred to a 500 mL UV-opaque single-neck flask and made up to 35 mL of solution. The solution was then cooled to 0°C in an ice bath, and DIPC dissolved in 15 mL of DMF was added dropwise via a pressure-equalizing dropping funnel with stirring, followed by washing down with 10 mL of DMF. A precipitate formed during the reaction. After addition, the cooling was removed, and the solution was stirred for 5 days.
[0094] For the work-up of the product, the precipitate was filtered and 100 mL of ethyl acetate and 100 mL of water were added to the yellowish solution. The aqueous phase was extracted three times by shaking with 150 mL of ethyl acetate each time. The combined organic phase was washed with 150 mL of water and twice with 150 mL of saturated aqueous sodium chloride solution. It was dried over magnesium sulfate and 0.1 g of BHT was added as a stabilizer. The solvent was removed under reduced pressure at 50° C. As a result, a colorless precipitate was precipitated. The solution was stored overnight at −26° C. The precipitate was filtered and washed with ice-cold ethyl acetate. The solvent was again removed under reduced pressure at 50° C. Then the product was subjected to column chromatography (EtAc:PE, 1:5).
[0095] Characterization Appearance: Colorless liquid Yield: 8.45g, 0.0361mol, 58.5% M = 234.25 g / mol
[0096] [ka]
[0097] 1 H NMR:(400MHz;CDCl3):δ[ppm]=1.99(m,3H,Hb),4.73(s,2H,Hc),5.21(s,2H,Hd),5.66(m,1H,Ha),6.23(m,1H,Ha),7.33-7.38(m,5H,He)
[0098] Example 9: (S)-2-Methacryloyloxypropionate benzyl ester (MAylO-L-La-Bn Reaction Equation
[0099] [ka]
[0100] reaction
[0101] [Table 8]
[0102] procedure The procedure was similar to the synthesis of 2-methacryloyloxyethanoate benzyl ester.
[0103] Characterization Appearance: Colorless liquid Yield: 28.31g, 0.1140mol, 59.4% M = 248.28 g / mol
[0104] [ka]
[0105] 1 H NMR:(400MHz;CDCl3):δ[ppm]=1.55(d,3H,Hd),1.97(m,3H,Hb),5.18(q,1H, Hc),5.20(s,2H,He),5.63(m,1H,Ha),6.20(m,1H,Ha),7.32-7.38(m,5H,Hf)
[0106] Example 10: 2-Methacryloyloxypropionate benzyl ester (MAylO-D,L-La-Bn) Reaction Equation
[0107] [ka]
[0108] reaction
[0109] [Table 9]
[0110] procedure The procedure was similar to the synthesis of 2-methacryloyloxyethanoate benzyl ester.
[0111] Characterization Appearance: Colorless liquid Yield: 8.19g, 0.0330mol, 45.8% M = 248.28 g / mol
[0112] [ka]
[0113] 1 H NMR:(400MHz;CDCl3):δ[ppm]=1.54(d,3H,Hd),1.97(m,3H,Hb),5.18(q,1H, Hc),5.20(s,2H,He),5.63(m,1H,Ha),6.21(m,1H,Ha),7.32-7.37(m,5H,Hf)
[0114] Example 11: Copolymerization DMPA initiator Reaction Equation
[0115] [ka]
[0116] reaction
[0117] [Table 10]
[0118] [Table 11]
[0119] [Table 12]
[0120] procedure The monomers MAylO-L-La-Bn and methyl methacrylate were columned through neutral alumina and then placed in a Schlenk tube. The initiator dissolved in benzene was then added and the tube was closed with a septum. The solution was subjected to three freeze-pump procedures. The Schlenk tube was placed in front of a UV lamp for 14 hours. The polymer was precipitated twice in ice-cold petroleum ether and dried by the Schlenk apparatus.
[0121] Characterization Appearance: Colorless solid
[0122] [Table 13]
[0123] [ka]
[0124] 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.66-1.20(6H,Hf),1.32-1.48(3H,Hd),1.62-2.08(4 H,He),3.43-3.62(3H,Hg),4.85-5.07(1H,Hc),5.07-5.24(2H,Hb),7.28-7.41(5H,Ha)
[0125] AIBN initiator Reaction Equation
[0126] [ka]
[0127] reaction
[0128] [Table 14]
[0129] [Table 15]
[0130] [Table 16]
[0131] procedure Ethyl acrylate and methyl methacrylate monomers were columned through neutral alumina to remove the stabilizer. They were then placed in a Schlenk tube. 2,2-azobis(2-methylpropionitrile) initiator was dissolved in benzene and transferred to the Schlenk tube. The Schlenk tube was closed with a glass stopper and subjected to three freeze-degassing procedures. The polymer was precipitated twice in ice-cold petroleum ether and dried by the Schlenk apparatus.
[0132] Characterization Appearance: Colorless solid
[0133] Since only the yield and mass distribution are important for studying initiator systems, 1 Characterization by 1 H NMR was omitted.
[0134] [Table 17]
[0135] Example 12: Poly(MAylO-L-La-Bn-co-MMA) Reaction Equation
[0136] [ka]
[0137] [ka]
[0138] reaction
[0139] [Table 18]
[0140] [Table 19]
[0141] [Table 20]
[0142] [Table 21]
[0143] procedure The monomers MAylO-L-La-Bn and methyl methacrylate were columned through neutral alumina and then placed in a Schlenk tube. The initiator dissolved in benzene was then added and the tube was closed with a septum. The solution was subjected to three freeze-degassing procedures. When DMPA was the initiator, the Schlenk tube was placed in front of a UV lamp for 14 hours; when AIBN was the initiator, the Schlenk tube was heated to 70°C for 16 hours. The polymer was precipitated twice in ice-cold petroleum ether and dried by the Schlenk apparatus.
[0144] Characterization Appearance: Colorless solid yield: Poly(MAylO-L-La-Bn-co-MMA)1:1(DMPA): 0.951g, 85%, Mn=3130g / mol, D=1.95 ポリ(MAylO-L-La-Bn-co-MMA)1:2(DMPA):0.455g, 84%, Mn=3130g / mol, D=1.83 ポリ(MAylO-L-La-Bn-co-MMA)2:1(DMPA):0.323g, 90%, Mn=2750g / mol, D=1.63 ポリ(MAylO-L-La-Bn-co-MMA)1:1(AIBN):1.523g, 99%, Mn=14480g / mol, D=2.42
[0145]
change
[0146] 1 H NMR: (400MHz; DMSO-d6): δ[ppm]=0.66-1.20(6H,Hf),1.32-1.48(3H,Hd),1.62-2.08(4 H,He),3.43-3.62(3H,Hg),4.85-5.07(1H,Hc),5.07-5.24(2H,Hb),7.28-7.41(5H,Ha)
[0147] Example 13: Poly(MAylO-D,L-La-Bn-co-MMA) Reflexive
[0148]
change
[0149]
change
[0150] Reaction
[0151]
Table 22
[0152]
Table 23
[0153] [Table 24]
[0154] [Table 25]
[0155] procedure The procedure was similar to the synthesis of MAylO-L-La-Bn-co-MMA polymer.
[0156] Characterization Appearance: Colorless solid yield: Poly(MAylO-D,L-La-Bn-co-MMA)1:1(DMPA): 0.809g, 72%, Mn=3200g / mol, D=1.78 Poly(MAylO-D,L-La-Bn-co-MMA)1:2(DMPA): 0.434g, 81%, Mn=2830g / mol, D=1.69 Poly(MAylO-D,L-La-Bn-co-MMA)2:1(DMPA): 0.333g, 93%, Mn=2330g / mol, D=1.74 Poly(MAylO-D,L-La-Bn-co-MMA)1:1(AIBN): 1.533g, 99%, Mn=14990g / mol, D=2.46
[0157] [ka]
[0158] 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.64-1.07(6H,Hf),1.30-1.49(3H,Hd),1.62-2.08(4 H,He),3.42-3.66(3H,Hg),4.85-5.06(1H,Hc),5.06-5.25(2H,Hb),7.23-7.46(5H,Ha)
[0159] Example 14: Poly(MAylO-Gly-Bn-co-MMA) Reaction Equation
[0160] [ka]
[0161] [ka]
[0162] reaction
[0163] [Table 26]
[0164] [Table 27]
[0165] [Table 28]
[0166] [Table 29]
[0167] procedure The procedure was similar to the synthesis of MAylO-L-La-Bn-co-MMA polymer.
[0168] Characterization Appearance: Colorless solid yield: Poly(MAylO-Gly-Bn-co-MMA) 1:1 (DMPA): 0.896 g, 79%, Mn = 2790 g / mol, D = 1.87 Poly(MAylO-Gly-Bn-co-MMA) 1:2 (DMPA): 0.391 g, 70%, Mn = 2680 g / mol, D = 1.66 Poly(MAylO-Gly-Bn-co-MMA) 2:1 (DMPA): 0.336 g, 92%, Mn = 2760 g / mol, D = 1.77 Poly(MAylO-Gly-Bn-co-MMA) 1:1 (AIBN): 1.460 g, 93%, Mn=9800 g / mol, D=2.63
[0169] [ka]
[0170] 1 H NMR:(400MHz;DMSO-d6):3[ppm]=0.61-1.26(6H,He),1.44-2.27(4H,Hd),3. 43-3.68(3H,Hf),4.55-4.82(2H,Hc),5.09-5.26(2H,Hb),7.24-7.44(5H,Ha)
[0171] Example 15: Poly(MAylO-L-La-Bn-co-EA) Reaction Equation
[0172] [ka]
[0173] reaction
[0174] [Table 30]
[0175] procedure The monomers MAylO-L-La-Bn and ethyl acrylate were columned through neutral alumina and then placed in a Schlenk tube. The initiator dissolved in benzene was then added and the tube was closed with a septum. The solution was subjected to three freeze-degassing procedures and then placed in front of a UV lamp for 14 hours. The polymer was precipitated three times in ice-cold petroleum ether and dried by the Schlenk apparatus.
[0176] Characterization Appearance: Colorless solid yield: Poly(MAylO-L-La-Bn-co-EA): 1.448g, 86%, Mn=7830g / mol, D=2.35
[0177] [ka]
[0178] 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.78-1.02(3H,Hf),1.02-1.22(3H,Hh),1.28-1.45(3H,Hd),1. 44-2.31(5H,He),3.80-4.12(2H,Hg),4.78-5.02(1H,Hc),5.02-5.23(2H,Hb),7.20-7.43(5H,Ha)
[0179] Example 16: Poly(MAylO-D,L-La-Bn-co-EA) Reaction Equation
[0180] [ka]
[0181] reaction
[0182] [Table 31]
[0183] procedure The procedure was similar to the synthesis of MAylO-L-La-Bn-co-EA polymer.
[0184] Characterization Appearance: Colorless solid yield: Poly(MAylO-D,L-La-Bn-co-EA): 1.234g, 74%, Mn=5930g / mol, D=2.15
[0185] [ka]
[0186] 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.79-1.00(3H,Hf),1.00-1.20(3H,Hh),1.25-1.46(3H,Hd),1. 46-2.35(5H,He),3.76-4.11(2H,Hg),4.78-5.01(1H,Hc),5.01-5.20(2H,Hb),7.18-7.42(5H,Ha)
[0187] Example 17: Poly(MAylO-Gly-Bn-co-EA) Reaction Equation
[0188] [ka]
[0189] reaction
[0190] [Table 32]
[0191] procedure The procedure was similar to the synthesis of MAylO-L-La-Bn-co-EA polymer.
[0192] Characterization Appearance: Colorless solid yield: Poly(MAylO-Gly-Bn-co-EA): 1.197 g, 76%, Mn=4680 / mol, D=2.28
[0193] [ka]
[0194] 1H NMR:(400MHz;DMSO-d6):δ[ppm]=0.73-1.03(3H,He),1.03-1.21(3H,Hg),1.24-2.38(5 H,Hd),3.79-4.14(2H,Hf),4.48-4.82(2H,Hc),5.03-5.23(2H,Hb),7.21-7.45(5H,Ha)
[0195] Example 18: Poly(MA-co-MMA) Reaction Equation
[0196] [ka]
[0197] reaction
[0198] [Table 33]
[0199] procedure The monomers of methacrylic acid and methyl methacrylate were columned through neutral alumina. They were then placed in a Schlenk tube and the initiator dissolved in benzene was added. The Schlenk tube was closed with a septum. The solution was subjected to three freeze-degassing procedures and then placed in front of a UV lamp for 14 hours. The polymer was precipitated twice in ice-cold petroleum ether and dried by the Schlenk apparatus.
[0200] Characterization Appearance: Colorless solid yield: Poly(MA-co-MMA): 3.166 g, 98%. Analysis by DMF-GPC was not possible as the polymer was not detected on the column used.
[0201] [ka]
[0202] 1H NMR:(400MHz;DMSO-d6):δ[ppm]=0.61-1.21(6H,Hc),1.60-2.03(4H,Hb),3.48-3.59(3H,Hd),12.29-12.55(1H,Ha)
[0203] Example 19: Poly(MA-co-EA) Reaction Equation
[0204] [ka]
[0205] reaction
[0206] [Table 34]
[0207] procedure The procedure was similar to the synthesis of MA-co-MMA polymer.
[0208] Characterization Appearance: Colorless solid yield Poly(MA-co-EA): 3.122 g, 96%. Analysis by GPC was not possible.
[0209] [ka]
[0210] 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.79-1.08(3H,Hc),1.10-1.24(3H,He),1.30-2.39(5H,Hb),3.84-4.16(2H,Hd),12.25-12.48(1H,Ha)
[0211] Example 20: RAFT polymerization of poly(MAylO-Gly-Bn-co-MMA) Reaction Equation
[0212] [ka]
[0213] reaction
[0214] [Table 35]
[0215] [Table 36]
[0216] procedure Methyl methacrylate and MAylO-Gly-Bn monomers were columned through neutral alumina. They were then placed in a Schlenk tube. AIBN initiator and 2-cyano-2-propyldodecyltrithiocarbonate RAFT agent were dissolved in benzene and transferred to the Schlenk tube. The Schlenk tube was closed with a glass stopper and the solution was subjected to three freeze-degassing procedures. The solution was heated at 70 °C for 4 days. The yellow solution was precipitated twice in ice-cold petroleum ether and the polymer was dried in the Schlenk apparatus.
[0217] Characterization 10kg / mol: 0.242g, 86%, Mn=5810g / mol, D=1.33, yellow solid 20kg / mol: 0.275g, 97%, Mn=10730g / mol, D=1.42, yellow solid
[0218] [ka]
[0219] 1 H NMR signal assignments: 10kg / mol: 1H NMR:(400MHz;DMSO-d6):δ[ppm]=0.68-1.09(172H,Hg),1.13-1.33(36H,Ha),1.33-2.11(104H,Hf),3. 23-3.29(2H,Hb),3.42-3.63(81H,Hh),4.56-4.79(69H,He),5.08-5.24(72H,Hd),7.25-7.43(180H,Hc) 20kg / mol: 1 H NMR:(400MHz;DMSO-d6):δ[ppm]=0.68-1.09(445H,Hg),1.13-1.33(26H,Ha),1.33-2.11(260H,Hf),3.23 -3.29(2H,Hb),3.42-3.63(225H,Hh),4.56-4.79(152H,He),5.08-5.24(161H,Hd),7.25-7.43(412H,Hc)
[0220] Example 21: RAFT polymerization of poly(MAylO-L-La-Bn-co-MMA) Reaction Equation
[0221] [ka]
[0222] reaction
[0223] [Table 37]
[0224] [Table 38]
[0225] procedure The procedure was similar to the synthesis of MAylO-Gly-Bn-co-MMA polymer by RAFT.
[0226] [ka]
[0227] Feature Rating 10kg / mol: 0.182g, 65%, Mn=4670g / mol, D=1.29, yellow solid 20kg / mol: 0.264g, 94%, Mn=10930g / mol, D=1.34, yellow solid 1H NMR シグナルのアサイン: 10kg / mol: 1 H NMR: (400MHz; DMSO-d6): δ[ppm]=0.67-1.08(126H,Hg),1.17-1.27(21H,Ha),1.27-1.48(91H,Hi),1.52-2.21(85 H,Hf),3.21-3.30(2H,Hb),3.42-3.66(58H,Hh),4.86-5.05(27H,He),5.05-5.24(53H,Hd),7.25-7.41(134H,Hc) 20kg / mol: 1 H NMR: (400MHz; DMSO-d6): δ[ppm]=0.67-1.08(317H,Hg),1.17-1.27(23H,Ha),1.27-1.48(194H,Hi),1.52-2.21(195 H,Hf),3.21-3.30(2H,Hb),3.42-3.66(162H,Hh),4.86-5.05(56H,He),5.05-5.24(107H,Hd),7.25-7.41(280H,Hc)
[0228] Example 22: Polymer modification Reflexive
[0229]
change
[0230] Reaction
[0231]
Table 39
[0232] Good luck The MA-co-MMA polymer and DMAP were placed in a 100 mL round bottom flask and dissolved in dioxane. DMAP and Gly-Bn were then added. The flask was heated at 70° C. for 2 days. The resulting solution was precipitated twice in ice-cold petroleum ether and dried by Schlenk apparatus.
[0233] Characterization Appearance: Colorless solid yield: Poly(MAylO-Gly-Bn-co-MMA): 0.165 g, 92%, Mn=5880 g / mol, D=3.83
[0234] 1 The H NMR spectrum and assignments correspond to those of poly(MAylO-Gly-Bn-co-MMA) in Scheme 42.
[0235] Example 23: Hydrogenation Reaction Equation
[0236] [ka]
[0237] reaction
[0238] [Table 40]
[0239] The molecular weight of the polymer is based on the repeat unit. The palladium / carbon catalyst has a palladium content of 5 wt%.
[0240] procedure The polymer was dissolved in 100 mL of ethyl acetate and transferred to a pressure reactor along with the Pd / C catalyst. The pressure reactor was sealed and H2 gas was introduced until a pressure of 40 bar was reached. The solution was heated to 40°C with stirring for 4 days. The reactor was then carefully opened and the dark liquid was filtered through a celite column. The colorless liquid was concentrated under reduced pressure and dried in a Schlenk apparatus. This resulted in a colorless, relatively porous solid.
[0241] Characterization Appearance: Colorless solid Yield: Quantitative
[0242] The present invention will now be described in detail with reference to the accompanying drawings. Figure 1: Apparatus for measuring the solubility of polymers as a function of pH. FIG. 2: Solubility measurements in diagram form for Eudragit® L 100 and similar polymers of the invention. FIG. 3: Solubility measurements in diagram form for Eudragit® L 100-55 and similar polymers of the invention. Figure 4: Release of paracetamol from capsules coated with Eudragit® L 100 and similar polymers. Figure 5: Release of paracetamol from capsules coated with Eudragit® L 100-55 and similar polymers Shows.
[0243] Example 24: Solubility Figures 2 and 3 show in the form of diagrams the results of solubility measurements of Eudragit L 100 and Eudragit L 100-55 type polymers in comparison with the polymers of the invention. As well as the measured values presented as points, the diagrams also show the a, pK, respectively, which have to be approximated. 1 / 2 and a pH-dependent function of the following type with parameters c:
number
number
[0244] For comparison, the inventors also synthesized polymers similar to Eudragit® L 100 and Eudragit® L 100-55 (referred to as "L 100 analog" and "L 100-55 analog", respectively) by free radical polymerization and tested their solubility. The "L 100 analog" and "L 100-55 analog" type polymers dissolve at a slightly lower pH than the Eudragit® polymers prepared by anionic polymerization. The solubility properties of the "L 100 analog" and "L 100-55 analog" polymers are believed to be due to their lower molecular weight.
[0245] Example 25: Paracetamol release Figures 4 and 5 show the results of measurements on the release of the active ingredient paracetamol from coated capsules under physiological conditions, i.e. at a temperature of 37°C, at a pH of 2 for the time interval 0-60 minutes and at a pH of 6.5 for time intervals over 60 minutes. The figures show the individual measured values or measurement points and a fitted curve. The fitted curve is based on the same type of function as described above in Example 24, but using time instead of pH as the independent variable.
[0246] As is evident from Figures 4 and 5, at pH 2 within the first 60 minutes, none of the tested capsule coatings releases paracetamol. Moreover, the measurements show that the active ingredient paracetamol is released from capsules coated with the polymers of the invention about 60 minutes and about 25 minutes earlier, respectively, compared to Eudragit® L 100 and Eudragit® L 100-55. The smaller time difference of about 25 minutes in the case of release from capsules coated with MAylO-Gly-co-EA, MAylO-L-La-co-EA and MAylO-D,L-La-co-EA compared to Eudragit® L 100-55 is due to the fact that the polymers in question dissolve at a pH in the range of 4.0 to 4.7 (see Example 24). In contrast, polymers of the MAylO-Gly-co-MMA, MAylO-L-La-co-MMA and MAylO-D,L-La-co-MMA types are already soluble at a pH in the range of 3.5 to 3.7.
[0247] List of abbreviations Abbreviations used in the context of this specification have the meanings given below, and some of the abbreviations for copolymers between brackets are preceded by the word "poly", for example, the abbreviations "MAylO-Gly-Bn-co-EA" and "Poly(MAylO-Gly-Bn-co-EA)" refer to the same copolymer. AIBN: Azoisobutyronitrile ATRP: Atom Transfer Radical Polymerization Eq.:Equivalent AS: acrylic acid residue (-CH[(C=O)-]CH2-) Ayl: acryloyl group (CH2=CH-(C=O)-) AylO: acryloyloxy group (CH2=CH-(C=O)-O-) AylO-Gly-Bn: 2-Acryloyloxyethanoate benzyl ester AylO-L-La-Bn: (S)-2-Acryloyloxypropionate benzyl ester AylO-D,L-La-Bn: 2-Acryloyloxypropionate benzyl ester AylO-Gly-Bn-co-EA: 2-Acryloyloxyethanoate benzyl-ethyl acrylate copolymer AylO-L-La-Bn-co-EA: (S)-2-Acryloyloxypropionate benzyl-ethyl acrylate copolymer AylO-D,L-La-Bn-co-EA: 2-Acryloyloxypropionate benzyl-ethyl acrylate copolymer AylO-Gly-Bn-co-MMA: 2-Acryloyloxyethanoate benzyl-methyl methacrylate copolymer AylO-L-La-Bn-co-MMA: (S)-2-Acryloyloxypropionate benzyl-methyl methacrylate copolymer AylO-D,L-La-Bn-co-MMA: 2-Acryloyloxypropionate benzyl-methyl methacrylate copolymer BHT: Butyl hydroxytoluene CFRP: Controlled Free Radical Polymerization DBU: 1,8-diazabicyclo[5.4.0]undec-7-ene DIPC: Diisopropylcarbodiimide D,L-La-Bn: 2-hydroxypropionate benzyl ester DMAP: 4-(N,N-dimethylamino)pyridine DMF: N,N-dimethylformamide DMPA: 2,2-dimethoxy-2-phenylacetophenone DMSO: Dimethyl sulfoxide EA: Ethyl acrylate residue (-CH[(C=O)OCH2CH3]CH2-) EMA: Ethyl methacrylate residue (-C(CH3)[(C=O)OCH2CH3]CH2-) EtAc: ethyl acetate Gly-Bn: Hydroxyethanoate benzyl ester GPC: Gel Permeation Chromatography L-La-Bn: (S)-2-hydroxypropionate benzyl ester MA: Methyl acrylate residue (-CH[(C=O)OCH3]CH2-) MA-co-MMA: Methacrylic acid-methyl methacrylate copolymer MA-co-EA: Methacrylic acid-ethyl acrylate copolymer MAS: methacrylic acid residue (-C(CH3)[(C=O)-]CH2-) MAyl: methacryloyl group (CH2=C(CH3)-(C=O)-) MAylO: methacryloyloxy group (CH2=C(CH3)-(C=O)-O-) MAylO-Gly-Bn: 2-Methacryloyloxyethanoate benzyl ester MAylO-L-La-Bn: (S)-2-Methacryloyloxypropionate benzyl ester MAylO-D,L-La-Bn: 2-Methacryloyloxypropionate benzyl ester MAylO-Gly-Bn-co-EA: 2-methacryloyloxyethanoate benzyl-ethyl acrylate copolymer MAylO-L-La-Bn-co-EA: (S)-2-methacryloyloxypropionate benzyl-ethyl acrylate copolymer MAylO-D,L-La-Bn-co-EA: 2-methacryloyloxypropionate benzyl-ethyl acrylate copolymer MAylO-Gly-Bn-co-MMA: 2-methacryloyloxyethanoate benzyl-methyl methacrylate copolymer MAylO-L-La-Bn-co-MMA: (S)-2-Methacryloyloxypropionate benzyl-methyl methacrylate copolymer MAylO-D,L-La-Bn-co-MMA: 2-methacryloyloxypropionate benzyl-methyl methacrylate copolymer MMA: Methyl methacrylate residue (-C(CH3)[(C=O)OCH3]CH2-) RAFT: Reversible Addition-Fragmentation Chain Transfer Polymerization
[0248] In the context of the present invention, the term "radical polymerization" encompasses methods such as free radical polymerization, controlled free radical polymerization (CFRP), reversible addition-fragmentation chain transfer polymerization (RAFT) and atom transfer radical polymerization (ATRP).
[0249] The copolymers of the present invention may be either random or block copolymers. Thus, the IUPAC term "-co-" in the polymer structural formulas of the present invention includes the IUPAC terms "-stat-" and "-block-".
[0250] Test Method In the present invention, the weight and weight distribution of the produced copolymers are measured by gel permeation chromatography (GPC or SEC) using dimethylformamide (DMF) at temperatures in the range of 25-30°C, standard pressure (985-1010 hPa) and standard humidity (40-100% rH) (Source: measurement station of the Institute for Atmospheric Physics, Johannes Gutenberg University of Mainz).
[0251] All chemicals and solvents were obtained from commercial suppliers (Acros, Sigma-Aldrich, Fisher Scientific, Fluka, Riedel-de-Haen, Roth) and used without further purification, except for drying of solvents and monomers, unless otherwise noted. Deuterated solvents were obtained from Deutero GmbH (Kastellaun, Germany).
[0252] Gel filtration chromatography (GPC or SEC) GPC or SEC measurements were performed according to DIN 55672-3 2016-01 at temperatures between 25 and 30 °C using an Agilent 1100 HPLC system equipped with a refractive index detector (Agilent 2160 Infinity RI detector), a UV detector (275 nm), an online viscometer, and a set of SDV columns (SDV 103, SDV 105, SDV 106) from Polymer Standard Service GmbH (hereafter referred to as PSS) as the solvent for the polymer being analyzed, and at a flow rate of 1 mL min -1 Dimethylformamide (DMF) was used as the eluent at a flow rate of 1000 s. The polymers to be analyzed, dissolved in DMF, were injected onto the GPC column by a Waters 717 plus autosampler. Calibration was performed using polystyrene standards from PSS. The elution profile was evaluated using WinGPC Unity software from PSS.
[0253] NMR spectroscopy A Bruker Avance II 400 (5 mm BBFO head with 400 MHz z-gradient and ATM) 1 H) or 101MHz ( 13 C) frequency, 1 H and 13 C NMR spectra were recorded. Kinetic in situ 1H NMR measurements were performed on a Bruker Avance III HD 400 spectrometer equipped with a 5 mm BBFO SmartProbe sensor (Z gradient probe), ATM and a SampleXPress 60 autosampler. Chemical shifts are reported in ppm and are based on the proton signals of the deuterated solvent.
[0254] Solubility and release of active ingredients The solubility of the inventive and known polymers of the Eudragit® class is determined by light transmission measurements at a temperature of 37° C. For this purpose, the polymer to be tested in each case is dissolved or suspended in a basic NaOH buffer bath at a concentration of 5 mg / mL, and the pH is gradually decreased by titration with a 0.1 M HCl solution. As the pH decreases, the polymer protonates and precipitates, scattering and attenuating the light.
[0255] The apparatus used for the solubility measurements is shown diagrammatically in Figure 1. The polymer solution or suspension is contained in a glass vessel with a lid and heated to 37 °C by a Peltier element. A magnetic stirrer is placed in the glass vessel, i.e. in the polymer suspension, and rotated by a magnetic drive. A light beam emitted by a light source passes through both side walls of the glass vessel and the polymer suspension between them, and hits an optoelectronic sensor, e.g. a photodiode, which measures the intensity of the transmitted light beam. Furthermore, the apparatus comprises a reservoir vessel for HCl (not shown in Figure 1), connected through a conduit to the interior of the glass vessel. In the conduit, a metering or titration valve (not shown in Figure 1) is placed to control the amount of HCl per unit time that is fed to the polymer suspension. Optical measurements of the transmittance are carried out using a Jasco V 640 spectrophotometer.
[0256] Furthermore, paracetamol-containing capsules were coated with the polymers of the invention, Eudragit® L 100 and Eudragit® L 100-55, and the release of paracetamol was tested, mimicking the physiological conditions in the gastrointestinal tract. The mimicking device used is, for example, available from Erweka GmbH and corresponds to Device 1 in the European Pharmacopoeia. At regular intervals, a very small amount of liquid compared to the content of the test vessel is removed and the concentration of paracetamol is measured photometrically at a wavelength of 243 nm.
[0257] A number of capsules containing paracetamol of the same shape are coated with the coating agents of the polymers of the invention of the Eudragit® L 100 and Eudragit® L 100-55 types, as well as the types MAylO-Gly-co-MMA, MAylO-L-La-co-MMA, MAylO-D,L-La-co-MMA, MAylO-Gly-co-EA, MAylO-L-La-co-EA and MAylO-D,L-La-co-EA. In the course of a series of tests, the viscosity of each polymer solution is adjusted so that the weight per unit area of the coating or the weight increase of the capsule due to the coating meets an accuracy of ±3%.
[0258] In each case, 3-4 capsules coated with one of the polymers to be tested are introduced into 900 mL of test solution, the pH of which is 2. To mimic the acidic environment of the stomach, the test solution containing the capsules is stirred for 60 minutes while maintaining the pH at 2 and the temperature at 37° C. The test solution is then replaced with a phosphate buffer solution, raising the pH to 6.5.
Claims
1. The structure: 【number】 [In the formula, MA is a methyl acrylate residue (-CH[(C=O)OCH 3 ]CH 2 -) and MMA is a methyl methacrylate residue (-C(CH 3 ) [(C=O)OCH 3 ]CH 2 -) and EA is the ethyl acrylate residue (-CH[(C=O)OCH 2 CH 3 ]CH 2 -) and EMA is an ethyl methacrylate residue (-C(CH 3 ) [(C=O)OCH 2 CH 3 ]CH 2 -) and AS is an acrylic acid residue (-CH[(C=O)-]CH 2 -) and MAS is a methacrylic acid residue (-C(CH 3 ) [(C=O)-]CH 2 -) and Rは、-CH 2 (C=O)-、-CH(CH 3 )(C=O)-、-CH(CH 2 CH 3 )(C=O)-、-C(CH 3 ) 2 (C=O)-、-C(CH 3 )(COCH 3 )(C=O)-、-CH(Ph)(C=O)-、-CH[(CH 2 ) 2 SCH 3 ](C=O)-、-CH(CH 2 COOH)(C=O)-、-CH(COOH)(C=O)-、-C(CH 2 COOH) 2 (C=O)-、-CH(COOH)CH(CH 2 COOH)(C=O)-または-CH(COOH)(CHOH)(C=O)-であり; n is 1, 2 or 3, and x, y, and z represent the relative molar ratios of monomer units, where 1≦x≦3, 1≦y≦3, and 0≦z≦3. A copolymer having the formula: The polydispersity of the copolymer is [0010] and The molar mass Mw of the copolymer is 4000 g mol -1 ≦Mw≦320000g・mol -1 The copolymer,
2. The structure: 【Chemistry 2】 The copolymer according to claim 1 , characterized in that it has the following formula:
3. The structure: 【Chemistry 3】 The copolymer according to claim 1 , characterized in that it has the following formula:
4. R is -CH 2 (C=O)- or -CH(CH 3 4. The copolymer according to claim 1, wherein the moiety is (C═O)—.
5. The polydispersity of the copolymer is [0025] The copolymer according to any one of claims 1 to 4, wherein
6. Use of the copolymers according to any one of claims 1 to 5 in pharmaceutical formulations or for coating tablets or capsules.
7. 1. A method for preparing a copolymer, comprising the steps of: The following steps: (a) selected from the group including hydroxyethanoic acid, 2-hydroxypropanoic acid, 2-hydroxybutanoic acid, 2-hydroxyisobutanoic acid, 2-hydroxy-2-methyl-3-oxobutanoic acid, phenylhydroxyethanoic acid, 2-hydroxy-4-methylthiobutanoic acid, 2-hydroxybutane-1,4-dicarboxylic acid, 2-hydroxypropanedicarboxylic acid, 2-hydroxypropane-1,2,3-tricarboxylic acid, hydroxypropane-1,2,3-tricarboxylic acid, or 2,3-dihydroxybutanedicarboxylic acid, and having the following structure: 【number】 [In the formula, Rは、-CH 2 (C=O)-、-CH(CH 3 )(C=O)-、-CH(CH 2 CH 3 )(C=O)-、-C(CH 3 ) 2 (C=O)-、-C(CH 3 )(COCH 3 )(C=O)-、-CH(Ph)(C=O)-、-CH[(CH 2 ) 2 SCH 3 ](C=O)-、-CH(CH 2 COOH)(C=O)-、-CH(COOH)(C=O)-、-C(CH 2 COOH) 2 (C=O)-、-CH(COOH)CH(CH 2 COOH)(C=O)-または-CH(CO OH)(CHOH)(C=O)-である。] The α-hydroxycarboxylic acid having the formula 2 )HC-COOH) or methacrylic acid ((CH 2 ) (CH 3 ) C—COOH) to give the following structure: 【number】 [In the formula, "Ayl" is acryloyl ((CH 2 )HC—CO—), and "MAyl" is methacryloyl ((CH 2 ) (CH 3 )C-CO-). obtaining a compound having the formula: (b) optionally monoesterifying or polyesterifying the compound (Ia) or (IIa) obtained in step (a) with an α-hydroxycarboxylic acid to obtain a compound having the following structure: 【number】 [Wherein, 2≦m≦3.] obtaining a compound of formula (I); (c) conjugating the compound (Ia), (Ib), (IIa) or (IIb) obtained in step (a) or (b) with a protecting group P to obtain the compound having the following structure: 【number】 [Wherein, 1≦n≦3.] obtaining a compound of formula (I); (d) Optionally, conjugating acrylic acid or methacrylic acid with a protecting group P to give the protected acrylic acid ((CH 2 )HC-COOP) or protected methacrylic acid ((CH 2 ) (CH 3 ) C-COOP); (e) polymerizing compound (Ic) or (IIc) in a relative molar ratio y with methyl acrylate, methyl methacrylate, ethyl acrylate or ethyl methacrylate in a relative molar ratio x and, optionally, with a protected acrylic acid or a protected methacrylic acid in a relative molar ratio z to give the following structure: 【number】 [In the formula, MA is a methyl acrylate residue (-CH[(C=O)OCH 3 ]CH 2 -) and MMA is a methyl methacrylate residue (-C(CH 3 ) [(C=O)OCH 3 ]CH 2 -) and EA is the ethyl acrylate residue (-CH[(C=O)OCH 2 CH 3 ]CH 2 -) and EMA is an ethyl methacrylate residue (-C(CH 3 ) [(C=O)OCH 2 CH 3 ]CH 2 -) and AS is an acrylic acid residue (-CH[(C=O)-]CH 2 -) and MAS is a methacrylic acid residue (-C(CH 3 ) [(C=O)-]CH 2 -) and 1≦x≦3, 1≦y≦3, and 0≦z≦3. obtaining a copolymer having the formula: (f) deprotecting and hydrolyzing the copolymer obtained in step (e) to give the following structure: 【number】 A copolymer having the formula: The polydispersity of the copolymer is [0030] and The molar mass Mw of the copolymer is 4000 g mol -1 ≦Mw≦320000g・mol -1 A step of obtaining the copolymer, The method comprising:
8. 8. The method according to claim 7, characterized in that in step (e) a free radical polymerization is carried out.
9. 8. The method according to claim 7, characterized in that in step (e) RAFT polymerization (Reversible Addition-Fragmentation Chain Transfer Polymerization) is carried out using a chain transfer agent.
10. The process according to any one of claims 7 to 9, characterized in that the deprotection and the hydrolysis in step (f) are carried out using a catalyst.
Citation Information
Patent Citations
Film-forming polymers and antifouling paints
JP2005520912A
Pigment dispersion for water-based gravure ink, water-based gravure ink and method for producing the same
JP2006131791A
Monodisperse Polymers Containing (Alkyl)Acrylic Acid Moieties, Precursors and Methods of Making and Applications Thereof
JP2008504411A
Acid-labile hyperbranched copolymer and associated photoresist composition and method of forming electronic device
JP2017110191A
Film-forming polymer and antifouling paint
WO2003080747A1
